Isomorfismo em sustentabilidade ambiental - Meira, Silvia Regina (2017)
Motivated by the growth of environmental sustainability in Brazil in the academic and business community, the growing number of companies adapting to environmental issues and access to the data of an environmental consultancy company in Brazil, this work aimed to analyze isomorphism in environmental sustainability. The purpose was to explain how these concepts are interrelated and understand the motivations that lead companies to adapt to environmental requirements. Through a sequence of three scientific studies (Study I ??? Isomorphism in Environmental Sustainability: where we are and where we are going ??? a bibliometric study on the theme; Study II ??? Theoretical Perspectives of Isomorphism in Environmental Sustainability: a bibliographic study; and Study III ??? By Free or Spontaneous Pressure: motivation for companies to adapt to environmental issues), the following research question was answered: How is isomorphism intertwined with environmental sustainability in motivations that lead companies to adapt to environmental issues? The results of Study I indicated three factors, enabling an understanding of the research on the theme, emphasizing the fundamental role of public policies, regulating agencies and society for the inclusion of environmental sustainability on the strategic agenda of companies. Study II pointed out six theoretical perspectives regarding the theme, identifying factors that may be related to the decision-making of companies in relation to the proactivity of their environmental actions. Study III highlighted that motivation in order to comply with legislation was mentioned in 65.53% of the works that were analyzed, indicating the formation of two groups related to the economic sector to which customers belonged. With the drafting of these studies, it can be seen that the theme has been studied little and that institutional pressures appear to point to isomorphism that, in time, may lead to behavior in search of social legitimacy and that may even show the financial and strategic advantages for companies in their search for environmental adaptation.